2007
DOI: 10.1097/qad.0b013e32825a69bd
|View full text |Cite
|
Sign up to set email alerts
|

Cervicovaginal HIV-1 and herpes simplex virus type 2 shedding during genital ulcer disease episodes

Abstract: Genital HSV-2 infection is associated with increased cervicovaginal and plasma HIV-1 RNA among co-infected women with genital ulcers, independently of the level of immunodeficiency, highlighting the close interaction between these two viruses and the role of HSV-2 as a co-factor for the sexual transmission of HIV-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
51
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 30 publications
2
51
0
Order By: Relevance
“…Briefly, eligible and consenting women with clinically verified GUD (including blisters and sores) were interviewed and examined genitally, and samples were obtained and tested as follows. Two swabs from the ulcer base were used to determine GUD etiology and to detect lesional HIV type 1 (HIV-1) RNA, using molecular methods (5,8,11,14); a cervicovaginal lavage (CVL) sample was collected to detect and quantify HSV-2 DNA and HIV-1 RNA in genital secretions, using real-time PCR (10); and blood samples were obtained for detection of HSV-2 antibodies (HerpeSelect; Focus Technologies, Cypress Hill, CA) and HIV-1 antibodies and for CD4 lymphocyte counts, as previously described (11). Serum samples obtained at days 14 and 28 from women who were HSV-2 seronegative at day 0 but positive for lesional and/or cervicovaginal HSV-2 DNA (i.e., with genital HSV-2 infection) were tested using HerpeSelect to detect possible HSV-2 seroconversion, and their enrollment (day 0) samples were tested for HSV-1 antibodies by HerpeSelect gG1 assay (Focus Technologies) to determine if these were cases of primary genital herpes (dually HSV-1-and HSV-2-seronegative samples) or nonprimary first-episode HSV-2 infection (HSV-1-seropositive and HSV-2-seronegative samples).…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, eligible and consenting women with clinically verified GUD (including blisters and sores) were interviewed and examined genitally, and samples were obtained and tested as follows. Two swabs from the ulcer base were used to determine GUD etiology and to detect lesional HIV type 1 (HIV-1) RNA, using molecular methods (5,8,11,14); a cervicovaginal lavage (CVL) sample was collected to detect and quantify HSV-2 DNA and HIV-1 RNA in genital secretions, using real-time PCR (10); and blood samples were obtained for detection of HSV-2 antibodies (HerpeSelect; Focus Technologies, Cypress Hill, CA) and HIV-1 antibodies and for CD4 lymphocyte counts, as previously described (11). Serum samples obtained at days 14 and 28 from women who were HSV-2 seronegative at day 0 but positive for lesional and/or cervicovaginal HSV-2 DNA (i.e., with genital HSV-2 infection) were tested using HerpeSelect to detect possible HSV-2 seroconversion, and their enrollment (day 0) samples were tested for HSV-1 antibodies by HerpeSelect gG1 assay (Focus Technologies) to determine if these were cases of primary genital herpes (dually HSV-1-and HSV-2-seronegative samples) or nonprimary first-episode HSV-2 infection (HSV-1-seropositive and HSV-2-seronegative samples).…”
Section: Methodsmentioning
confidence: 99%
“…HSV-2 infection, the leading cause of genital ulcers, is common among HIV-1-infected women, with HSV-2 seroprevalence ranging from 75% to over 95% in sub-Saharan Africa [4][5][6]. Clinical and sub-clinical HSV-2 reactivation is associated with higher HIV-1 plasma and genital RNA levels [5,[7][8][9][10][11], demonstrating that HSV-2 increases HIV-1 replication. Although clinical trials have shown that HSV-2 suppressive therapy significantly reduces plasma and cervical HIV-1 RNA levels [12][13][14][15][16][17], it did not decrease risk of heterosexual HIV-1 transmission [15].…”
mentioning
confidence: 99%
“…Women are twice as likely to become infected with HIV during heterosexual sex as are men (37,38), with transmission risks for both sexes increasing with higher plasma viral loads (9). Although plasma concentrations of HIV virions are a strong predictor of transmission rates, local mucosal factors such as genital inflammation and concurrent sexually transmitted infections are also strongly associated with both increased shedding of virus at the genital tract and greater susceptibility to infection via the genital mucosa (4,6,17,30). Although immunological activation in response to invading pathogens is a crucial component of protective immunity, such responses may ironically also contribute to HIV pathogenesis by providing the virus with a steady supply of susceptible target cells (16).…”
mentioning
confidence: 99%